2020
DOI: 10.3390/ijms21030712
|View full text |Cite
|
Sign up to set email alerts
|

Does Allergy Break Bones? Osteoporosis and Its Connection to Allergy

Abstract: Osteoporosis and allergic diseases are important causes of morbidity, and traditionally their coexistence has been attributed to causality, to independent processes, and they were considered unrelated. However, the increasing knowledge in the field of osteoimmunology and an increasing number of epidemiological and biological studies have provided support to a correlation between bone and allergy that share pathways, cells, cytokines and mediators. If the link between allergic pathology and bone alterations app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…We tried to look through pathogenetic mechanisms, epidemiological, and clinical data to highlight the most up-to-date knowledge. The complexity of allergic inflammation in its several forms [100] supports the need for recognizing sex-gender associated differences to better understand the pathobiology of the allergic diseases. The ultimate goal is to define and understand these differences or their absence and improve prevention, diagnosis, care and treatment of both women and men.…”
Section: Discussionmentioning
confidence: 99%
“…We tried to look through pathogenetic mechanisms, epidemiological, and clinical data to highlight the most up-to-date knowledge. The complexity of allergic inflammation in its several forms [100] supports the need for recognizing sex-gender associated differences to better understand the pathobiology of the allergic diseases. The ultimate goal is to define and understand these differences or their absence and improve prevention, diagnosis, care and treatment of both women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of patients with IgE-dependent FA have experienced at least one serious anaphylactic reaction, especially in childhood and adolescence [11,19]. The variability of clinical expressions and the complexity of the underlying immunological mechanisms contribute to making diagnosis often difficult and complicate the studies on the epidemiology of FA [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Epidemiologymentioning
confidence: 99%
“…Although each type of food may constitute a potential allergen, the list of foods responsible for the great majority of cases, especially the most clinically severe forms, is relatively short [3,10,24]. In industrialized countries the foods most frequently responsible for allergies in children are cow'smilk, eggs, wheat, fish and shellfish, peanuts, walnuts, and soybeans.…”
Section: Epidemiologymentioning
confidence: 99%
“…IL-33-and ST2-knockout mice show homeostatic dysregulation of granulocyte responses in both the blood and bone marrow compartments, suggesting that IL-33 acts on many other cell types besides bone cells, all able to indirectly influence the bone. For example, IL-33 precedes IL-5 in regulating eosinophil commitment [75], contributing to the complex cytokine network driving both allergic and bone diseases [76]. Shulze et al demonstrated that IL-33 directly stopped osteoclast formation from bone marrow precursor cells [70], and Zaiss et al described a shift in the differentiation of myeloid bone marrow progenitors from osteoclasts to macrophages [77].…”
Section: The Role Of Il-33 In the Immunoskeletal Interfacementioning
confidence: 99%